Technology tools, including software and websites, which facilitate the translation of different documents from english to spanish and from spanish to english. - Arriola Santamaría, José Diego; Ascencio Rivera, Daniel; Hidalgo Lemus, Carlos Enrique; Galdámez Garcia, Carlos Indalecio (2024)
It is well known that translation is the process of transferring a text from a source language into the target language. The following text is to summarize how essential the translation process is when having the ability of speaking more than one language. It is essential to consider the use of specific tools in order to keep the original meaning of each document, to reach this result many techniques can be use. By following the instruction from the techniques and tools, these techniques have been proposed in order to be accurate at the moment to adapt the source language. In relation to translation, this does not mean converting the text by a human being. It is also focusing on the tools which the translator can use. Everyone should focus on how translation is playing a big role in the world; this is making the difference. Taking into consideration that nowadays all books are written in a source language, these tools are going to be helpful since the largest documents can be translated in an accurate way. To conclude about translation which is one of the most common processes since these techniques will facilitate people at the moment to communicate. Translation methods relate to whole texts, translation procedures are used for sentences and the smaller units of language. These methods give the choice and opportunity to engage people to keep learning and discovering other languages. Key words: Source language; Target language ; Books ; Speaking; Translation Tools; Translation Techniques; Translation process; Interpretation.